DNA barcoding of mayflies (Insecta: Ephemeroptera) from South India. Issue 1 (1st January 2016) - Selvakumar, Chellappa; Sivaramakrishnan, Kumbakonam Govindarajaiyer; Janarthanan, Sundaram
Abstract: In this study, DNA barcodes were generated for 40 species belonging to 32 genera under 10 families of Ephemeroptera from South India. Nucleotide sequence divergences were calculated using the Kimura two-parameter distance model and a neighbour-joining analysis was performed to provide a graphic display of the patterns of divergence among the species. This study demonstrates that COI barcoding is effective in discriminating among the mayfly species of South India, and provides a reference library for their future molecular identification.